Carbon Nanotubes for Slope Stabilization of Silty Soil - Hussain Ahmadi; Alfrendo Satyanaga; Saltanat Orazayeva; Gulnur Kalimuldina; Harianto Rahardjo; Zhai Qian; Jong Kim (Infrastructures)
Landslides are a common occurrence that results in both human and financial losses each year around the world. The conventional methods use a variety of techniques, such as the application of lime, cement, and fly ash, for slope stabilization. Nevertheless, all these materials, to some extent, have their own shortcomings. In this study, multi-walled carbon nanotubes (MWCNTs) application was investigated for slope stabilization. Extensive saturated and unsaturated laboratory testing as well as numerical analyses were conducted in this study for both scenarios of soil with and without MWCNTs. The result from unsaturated testing demonstrates that the air-entry value and saturated volumetric water content of soil with MWCNTs increased compared to soil without MWCNTs, while the unsaturated permeability of soil stabilized with MWCNTs decreased. The result from the SEEP/W analysis during rainfall shows that the pore-water pressure (PWP) in the slope without carbon nanotubes was higher than the PWP in the slope with MWCNTs in the surface area. During rainfall, the factor of safety (FoS) of the slope without MWCNTs declined rapidly and at a high rate according to the Slope/W analysis, whereas the FoS of the slope with MWNCTs only changed slightly and remained safe when compared to the non-stabilized slope.